New species of Medetera (Diptera: Dolichopodidae, Medeterinae) from Tibet - Tang, Chufei; Wang, Baohai; Yang, Ding (Zootaxa, 2015)
Only one species of Medetera Fischer von Waldheim was known to occur previously in Tibet. Here the following three species of Medetera are described as new to science: Medetera exornata sp. nov., Medetera furva sp. nov. and Medetera sinuosa sp. nov. The first two species belong to the apicalis group, and the last one belongs to the diadema-veles group. A key to the species of Medetera from the Himalayas is provided.